Unseen Urgency? Projections of extreme sea level events and stakeholder perception on the German North Sea islands of Norderney and Borkum - Lawrenz, Christiane; Witt, Gesa; Bernzen, Amelie; Braun, Boris (ERDKUNDE, 2025)
Sea Level Rise (SLR) has been widely acknowledged as a long-term challenge that threatens large numbers of coastal areas. Yet, extreme sea-level rise (ESLR) often has an even more immediate impact on planning local coastal defense infrastructure. This is also the case for the German North Sea islands, including Norderney and Borkum. Existing studies often lack detailed localized projections and comprehensive assessments, creating a gap in precise impact estimation and stakeholder engagement. Understanding stakeholder perceptions of urgency is critical for informed decision-making. This article aims to address this gap by providing high-resolution ESLR projections and examining the perceptions and priorities of different stakeholder groups on these islands. A hybrid modeling approach, integrating physical and geostatistical components, was employed to project ESLR for the years 2050 and 2100 under various Representative Concentration Pathways. Furthermore, semi-structured interviews with stakeholders from tourism, politics, administration, and environmental management were conducted to capture the range of attitudes and concerns regarding ESLR and related adaptation measures. The results indicate a potential sea level rise of more than 2 meters for Norderney and Borkum by 2100. Yet, stakeholder interviews reveal a wide disparity in perceptions; environmental actors express high urgency, while others, particularly among those in the tourism sector, see ESLR as a more distant concern, leading to a reduced motivation for immediate action as other, more pressing short-term challenges are prioritized. Our findings highlight the need for policy strategies that integrate economic and environmental goals, ensuring effective adaptation measures that address both current and future challenges.